Genetic basis of the difference in alcohol dehydrogenase expression between Drosophila melanogaster and Drosophila simulans. - Laurie, C C (1990)
Drosophila melanogaster and its sibling species, Drosophila simulans, differ in expression of the enzyme alcohol dehydrogenase (ADH). Adult melanogaster flies that are homozygous for the Slow allozyme have approximately twice the level of ADH activity and crossreacting material as simulans adults. There is no corresponding difference in ADH mRNA, however, so this difference in ADH protein level is evidently due to a difference in the rate of translation of the two RNAs and/or to a difference in protein stability. Here we report an interspecific gene-transfer experiment, using P-element transformation, to determine whether this expression difference is due to genetic background differences between the species (trans-acting modifiers) or to cis-acting factors within the Adh gene. When the Adh genes from D. melanogaster and D. simulans are put into the same genetic background, there is no detectable difference in their level of expression. The level is relatively high in the melanogaster background and relatively low in the simulans background. Therefore, the interspecific difference in Adh expression is due entirely to trans-acting modifiers, in spite of the many sequence differences between the Adh genes of the two species, which include two amino acid substitutions.